Price Identification And Financial Feasibility Study of Hydroponic Agriculture Iot Solution Launch Project at PT XYZ - Irawan, Anjeli Siti Maliska; Kitri, Mandra Lazuardi (Integrasi Sains Media, 2023)
Since 2015, the Internet of Things technology has grown significantly, reaching over 400 million users by 2022 in Indonesia. Recognizing the potential, PT XYZ, an innovative Indonesian telecommunications company, intends to launch an IoT solution for hydroponic agriculture. The launch project requires an initial investment of around Rp 500 million. Given that amount, PT XYZ aims to determine the selling price using a value-based pricing strategy and assess the project's financial feasibility and risks before proceeding. Primary and secondary data will be utilized in this research to determine the customer's willingness to pay (WTP), Capital budgeting cash flow, which includes the hypothetical price of IoT, calculating the weighted average cost of capital (WACC), free cash flow to the firm (FCFF), and terminal value. The study used various capital budgeting techniques, such as net present value (NPV), profitability index, payback period, internal rate of return (IRR), and Excel's goal seek feature, to determine the IoT solution's pricing. A risk analysis using sensitivity and Monte Carlo simulations have conducted. The research finds that the present value of benefits, or WTP, for the IoT solution, is Rp 90,708,238. Considering PT XYZ's targeted internal rate of return of 20%, the determined selling price is Rp 20,120,408, which lies within the customer's WTP, making the project feasible. Capital budgeting techniques show a payback period of 4.08 years, an NPV of Rp 3,424,935,505, and a profitability index of 8.21 over five years, indicating positive outcomes. However, the sensitivity analysis reveals that a change in product price, cost of goods sold, and salary expenses will significantly impact the NPV, resulting in a 12.69% risk, with profitability remaining high at 87.31%. In conclusion, PT XYZ's hydroponic agriculture IoT solution launch project is considered feasible, considering potential risks and mitigation strategies.